Fast‐rate output feedback control system design with adaptive output estimator for nonuniformly sampled multirate systems. (22nd May 2013) - Mizumoto, I.; Fujimoto, Y.
SUMMARY: Multirate sampled system can be seen in many industries and several kinds of control method using lifting method have been proposed. Unfortunately, it was difficult to deal with nonuniformly sampled multirate systems. In this paper, we will propose a design scheme of output feedback control with a simple structure for nonuniformly sampled systems based on almost strictly positive real properties. A design method of a fast‐rate output feedback control system for nonuniformly sampled multirate systems with a fast uniform input updating rate and slow nonuniform output sampling rates. An adaptive output estimator will be proposed so as to realize a fast‐rate output feedback control for nonuniformly sampled systems at the fast sampling period of the input updating rate, and then, a design scheme of a fast‐rate adaptive output feedback control at the fast sampling period of the input updating rate will be proposed for nonuniformly sampled systems utilizing the proposed adaptive output estimator. We also analyze the stability of the obtained fast‐rate output feedback control system based on almost strictly positive real properties of the controlled system. Copyright © 2013 John Wiley & Sons, Ltd.